Development of Rotational Symmetry Media Using Project-Based Learning to Enhance Mathematical Understanding - Murni, Sukma; Ruqoyyah, Siti (Universitas Suryakancana, 2025)
This research is motivated by the low level of mathematical concept understanding among elementary school students. The aim of this study is to investigate the improvement in mathematical concept understanding in third-grade students on the topic of rotational symmetry, taught using a rotational symmetry board media and Project-Based Learning (PBL). The method employed is Research and Development (R&D) to develop a learning media designed to assist students in solving problems related to this material. The study was conducted at Budi Asih Elementary School, where the students exhibit low mathematical concept understanding. The subjects of this study are third-grade students, divided into a limited trial class with 10 students and an extended trial class with 20 students. The instruments used to gather research data include non-test methods such as documentation study, teacher interviews, questionnaires for teachers and students, media validation, content validation, practitioner validation, observation, and a test with 5 questions assessing students' mathematical concept understanding in rotational symmetry. These instruments were then tested for validity, reliability, difficulty index, and discriminating power. The results indicate that there was an improvement in students' mathematical concept understanding in the rotational symmetry topic using the rotational symmetry board media with Project-Based Learning, as shown by the average pretest and posttest results in both the limited and extended trial classes.